Poor Glycemic Control and the Contributing Factors Among Type 2 Diabetes Mellitus Patients Attending Outpatient Diabetes Clinic at Mbarara Regional Referral Hospital, Uganda - Patrick, Nsheka Bonny; Yadesa, Tadele Mekuriya; Muhindo, Rose; Lutoti, Stephen (My University, 2021)
Background: Glycemic control is associated with long-term complications in type 2 diabetes management. However, updated reports on glycemic control that are crucial to reducing diabetes mellitus complications remain scarce. Objective: The objective of this study is to evaluate glycemic control and contributing factors among type 2 diabetes mellitus patients attending the outpatient diabetic clinic at Mbarara Regional Referral Hospital. Methods: A cross-sectional study was conducted at Mbarara Regional Referral Hospital outpatient diabetes clinic between July and October 2020. Participants were subjected to a questionnaire-based interview and glycosylated hemoglobin (HbA1C) was determined as a marker of glycemic control among participants. The collected data was entered into and analyzed by Stata version 13. The odds ratio was used to determine the strength of association between variables. The cut-off value for all statistical significance tests was set at p<0.05 with CI of 95%. Results: A total of 223 participants were interviewed, and the majority (188, 84.3%) had poor glycemic control (HbA1C ≥7%). Importantly, 81.7% (49/60) and 90.0% (99/110) of those who did not adhere to diet and physical exercise recommendations respectively, had poor glycemic control. Multivariate logistic regression revealed that poor glycemic control was more prevalent among participants aged 25–60 years (AOR=4.48, 95%CI: 1.56–14.50, p-value=0.009) and those aged above 60 years (AOR=4.28, 95%CI: 1.18–15.58, p-value= 0.03) compared to the youth, 18–24 years of age. Conclusion: The prevalence of poor glycemic control among type 2 diabetes patients in this study is high and patient’s age was identified to be an independent risk factor. We recommend any intervention by the hospital that promotes diabetes education and optimizes lifestyle and medication adherence; ultimately to achieve good glycemic control especially for adult patients.
Diabetes, Metabolic Syndrome and Obesity: Targets and Therapy
Keywords: Type 2 diabetes mellitus; poor glycemic control; glycosylated hemoglobin A1C